Field reports form for submitting seasonal observations of Iowa birds, Francis L. Moore, fall 1986 - Moore, Francis L.et al (1986)
List of birds and locations contributed by Francis L. Moore with observers Robert I. Cecil, Thomas H. Kent and Robert K. Myers. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed